Anti-obesity drugs alone or combined with exercise training in the management of obesity: a systematic review with meta-analysis - Marmett Bruna; da Silva Igor; Lira Fabio; Dorneles Gilson (Translational Exercise Biomedicine, 2025)
Here we compare the efficacy of anti-obesity drugs alone or combined with exercise training on body weight and exercise capacity of obese patients. Randomized clinical trials that assessed the impact of any anti-obesity drug alone or combined with exercise training on body weight, body fat, fat-free mass and cardiorespiratory fitness in obese patients were retrieved from Pubmed and EMBASE up to May 2024. Risk of bias assessment was performed with RoB 2.0, and the GRADE approach assessed the certainty of evidence (CoE) of each main outcome. We included four publications summing up 202 patients. Two publications used orlistat as an anti-obesity drug treatment, while the other two adopted GLP-1 receptor agonist (liraglutide or tirzepatide) as a pharmacotherapy for weight management. Orlistat combined with exercise was superior to change body weight (mean difference (MD): −2.27 kg; 95 % CI: −2.86 to −1.69; CoE: very low), fat mass (MD: −2.89; 95 % CI: −3.87 to −1.91; CoE: very low), fat-free mass (MD: 0.56; 95 % CI: 0.40–0.72; CoE: very low), and VO2Peak (MD: 2.64; 95 % CI: 2.52–2.76; CoE: very low). GLP-1 receptor agonist drugs combined with exercise had a great effect on body weight (MD: −3.96 kg; 95 % CI: −5.07 to −2.85; CoE: low), fat mass (MD: −1.76; 95 % CI: −2.24 to −1.27; CoE: low), fat-free mass (MD: 0.50; 95 % CI: −0.98 to 1.98; CoE: very low) and VO2Peak (MD: 2.47; 95 % CI: 1.31–3.63; CoE: very low). The results reported here suggest that exercise training remains an important approach in weight management when combined with pharmacological treatment.